Ruby cookbook - Carlson, Lucas; Richardson, Leonard (O'Reilly Media, 2015)
Why spend time on coding problems that others have already solved when you could be making real progress on your Ruby project? This updated cookbook provides more than 350 recipes for solving common problems, on topics ranging from basic data structures, classes, and objects, to web development, distributed programming, and multithreading. Revised for Ruby 2.1, each recipe includes a discussion on why and how the solution works.
Includes index. - Print version record
Keywords: Ruby (Computer program language); Application software -- Development; Object-oriented programming (Computer science); Ruby (Langage de programmation); Logiciels d'application; Développement; Programmation orientée objet (Informatique); COMPUTERS; Programming Languages; C#; COMPUTERS; Programming Languages; Java; COMPUTERS; Programming Languages; Pascal; Application software; Development